Data Cultures: a scoping literature review - Gillian Oliver; Jocelyn Cranefield; Spencer Lilley; Matthew Lewellen (Information Research: An International Electronic Journal)
Introduction. This paper reports the outcomes from a literature review of the concept of data cultures as the first step in extending the body of knowledge relating to information culture in the information science domain and raising awareness of the need for further research.